SEISMIC FRAMES OF INDUSTRIAL STRUCTURES IN VIEW OF USE DAMAGES AND IN ITS RECOVERY - , К. М. (Municipal economy of cities. Series: «Economy science», 2013)
The article presents seismic stability calculations for a transverse frame of an industrial structure made by “Lira”. It also analyses the structure’s behavior at 7, 8, 9 point seismicity considering functional damage and restoration to designed parameters as gives conclusions of the research.